All-for-One Tourism: The Transformation and Upgrading Direction of Regional Tourism Industry - Feng, Xiaoxu (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2017)
All-for-One Tourism is a new planning concept proposed by Chinese tourism management practitioners. Based on the present situation of tourism industry development, the new planning concept is to guide the transformation and upgrading of tourist destinations. The development level of all-for-one tourism represents the maturity of regional tourism industry. China has been actively promoting the all-for-one tourism work since 2016. In the process of promoting transformation from scenic spots to all-for-one tourism, we need to grasp development law, strengthen problem-oriented principle and consider comprehensive impacts.